TMOES: a CORBA service middleware enabling high-level real-time object programming - Kim, K.H.; Liu, J.Q.; Miyazaki, H.; Shokri, E.H. (5th International Symposium on Autonomous Decentralized Systems (ISADS 2001), 2001)
Extending the CORBA programming and execution environments to support real-time distributed applications is a subject of growing interest to both research and industry. The time-triggered message triggered object (TMO) programming scheme has been established to remove the severe limitations of conventional object structuring techniques in developing real-time distributed applications. To facilitate the construction of TMO-structured real-time distributed applications consisting of CORBA-compliant components, a middleware named TMO Execution Support (TMOES) has been created. TMOES instantiations residing in cooperating computing nodes also communicate among themselves only via ORBs conforming to the standard specifications. TMOES instantiations cooperate among themselves to support timely execution of TMO methods and interactions among remote TMOs. This paper presents the architecture and an implementation model of TMOES.